Clinical trial protocol: phase 3, multicenter, randomized, double-blind, placebo-controlled, parallel-group, efficacy, and safety study comparing EG-1962 to standard of care oral nimodipine in adults with aneurysmal subarachnoid hemorrhage [NEWTON-2 (Nimodipine Microparticles to Enhance Recovery While Reducing TOxicity After SubarachNoid Hemorrhage)] - Hänggi, Daniel; Etminan, Nima (Neurocritical care, 2019)
BackgroundNimodipine is the only drug approved in the treatment of aneurysmal subarachnoid hemorrhage (aSAH) in many countries. EG-1962, a product developed using the Precisa™ platform, is an extended-release microparticle formulation of nimodipine that can be administered intraventricularly or intracisternally. It was developed to test the hypothesis that delivering higher concentrations of extended-release nimodipine directly to the cerebrospinal fluid would provide superior efficacy compared to systemic administration.ResultsA Phase 1/2a multicenter, controlled, randomized, open-label, dose-escalation study determined the maximum tolerated dose and supported the safety and tolerability of EG-1962 in patients with aSAH. EG-1962, 600 mg, was selected for a pivotal, Phase 3 multicenter, randomized, double-blind, placebo-controlled, parallel-group efficacy, and safety study comparing it to standard of care oral nimodipine in adults with aSAH. Key inclusion criteria are patients with a ruptured saccular aneurysm repaired by clipping or coiling, World Federation of Neurological Surgeons grade 2-4, and modified Fisher score of > 1. Patients must have an external ventricular drain as part of standard of care. Patients are randomized to receive intraventricular investigational product (EG-1962 or NaCl solution) and an oral placebo or oral nimodipine in the approved dose regimen (active control) within 48 h of aSAH. The primary objective is to determine the efficacy of EG-1962 compared to oral nimodipine.ConclusionsThe primary endpoint is the proportion of subjects with favorable outcome (6-8) on the Extended Glasgow Outcome Scale assessed 90 days after aSAH. The secondary endpoint is the proportion of subjects with favorable outcome on the Montreal Cognitive Assessment 90 days after aSAH. Data on safety, rescue therapy, delayed cerebral infarction, and health economics will be collected.Trail registration NCT02790632.
First online: 16 July 2018
Gesehen am 24.10.2019